2019
DOI: 10.1109/tsp.2019.2916046
|View full text |Cite
|
Sign up to set email alerts
|

Estimation From Quantized Gaussian Measurements: When and How to Use Dither

Abstract: Subtractive dither is a powerful method for removing the signal dependence of quantization noise for coarselyquantized signals. However, estimation from dithered measurements often naively applies the sample mean or midrange, even when the total noise is not well described with a Gaussian or uniform distribution. We show that the generalized Gaussian distribution approximately describes subtractively-dithered, quantized samples of a Gaussian signal. Furthermore, a generalized Gaussian fit leads to simple estim… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…Note that the equality in the above inequality happens when ξ = ξ i . Thus, the MM iteration cycle in (11) approaches the ML estimation of ξ as long as the initial value L( ξ 0 ) is smaller than all local minima in L( ξ). Next, we recall the following lemma in [14] to construct a suitable majorizing function of L( ξ).…”
Section: Majorization-minimization Based Maximum Likelihood Estimationmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the equality in the above inequality happens when ξ = ξ i . Thus, the MM iteration cycle in (11) approaches the ML estimation of ξ as long as the initial value L( ξ 0 ) is smaller than all local minima in L( ξ). Next, we recall the following lemma in [14] to construct a suitable majorizing function of L( ξ).…”
Section: Majorization-minimization Based Maximum Likelihood Estimationmentioning
confidence: 99%
“…One well-practiced option to develop lightweight algorithms is to apply low-bit quantization [11]- [13], including the extreme case of one-bit data [14]- [16]. Using quantized observations in DPD is a promising option for saving network traffic [17], with the one-bit processing approach recently adopted in [18].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study ( [26]) explores the use of quantization with dithering to determine which distribution the substractive dithering follows. The work presented in [27] shows that the use of dithering with quantization could be improved if an orthogonal transformation was performed on the quantizer input prior to the quantization process.…”
Section: Ditheringmentioning
confidence: 99%
“…Rapp et al [29] demonstrated the effectiveness of a subtractive-dithered time-correlated single-photon-counting ranging system for improving the depth resolution. Next, the dithered imaging generalised Gaussian instrument response function (IRF) approximation and exponentially modified Gaussian IRF model provided accurate ranging results from sub-bin delayed imaging [30][31][32]. Chang et al [33] achieved kilometre-scale dither superresolution depth imaging.…”
Section: Introductionmentioning
confidence: 99%